2011
DOI: 10.1021/jf104640k
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Phenolic Compositions of Lentil (Lens culinaris var. Morton) Extract and Its Fractions

Abstract: Phenolic compounds were extracted from Morton lentils using acidified aqueous acetone. The crude Morton extract (CME) was applied onto a macroresin column and desorbed by aqueous methanol to obtain a semi-purified Morton extract (SPME). The SPME was further fractionated over Sephadex LH-20 column into five main fractions (Fr I – Fr V). The phytochemical contents such as total phenolic content (TPC), total flavonoid content (TFC), and condensed tannin content (CTC) of the CME, SPME, and its fractions were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(172 citation statements)
references
References 32 publications
10
154
3
1
Order By: Relevance
“…For lentils, as shown in Table 3, the medium type had the highest amounts of all of the phenolic compounds compared to the other varieties considered here. The TPC of our varieties, as averaged over two years and two treatments, varied from 4.23 mg CE/g for the small green lentils, to 5.82 mg CE/g for the medium type of lentils, and these are in the same ranges of values reported in other studies: Zou et al [43] reported a TPC of 6.93 mg GAE/g in the lentil var. Morton, which is similar to that reported by Xu et al [44] (6.96 mg GAE/g, as the average of 11 varieties).…”
Section: Antioxidant Compounds and Antioxidant Activitysupporting
confidence: 86%
“…For lentils, as shown in Table 3, the medium type had the highest amounts of all of the phenolic compounds compared to the other varieties considered here. The TPC of our varieties, as averaged over two years and two treatments, varied from 4.23 mg CE/g for the small green lentils, to 5.82 mg CE/g for the medium type of lentils, and these are in the same ranges of values reported in other studies: Zou et al [43] reported a TPC of 6.93 mg GAE/g in the lentil var. Morton, which is similar to that reported by Xu et al [44] (6.96 mg GAE/g, as the average of 11 varieties).…”
Section: Antioxidant Compounds and Antioxidant Activitysupporting
confidence: 86%
“…The scientific literature has reported that the proteins from some legumes (soy, lentils and beans, amongst others) have antioxidant properties (DÁVILA et al, 2003;ZOU et al, 2011). However, in this study, the addition of quinoa flour was associated with an increase in oxidation of the sausages.…”
Section: Resultscontrasting
confidence: 56%
“…The research for antioxidants from natural sources aims to identify compounds that may help to prevent oxidative damage in the body and contribute to the prevention of noncommunicable diseases 15,16 . The by-products of J. curcas such as leaves have not been comprehensively studied, therefore limited information is available on the feasible application of the meal as a potential source of bioactive compounds 9 .…”
Section: Introductionmentioning
confidence: 99%